1994
DOI: 10.1002/aic.690401212
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of benzyl alcohol using hypochlorite ion via phase‐transfer catalysis

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…19 Three cases are considered, namely, (i) measurements of all species in both phases, (ii) measurements of the kinetic species and equilibrium components in the phase where the instantaneous equilibria take place (phase G), and (iii) measurements of a mix of kinetic species, equilibrium components, and equilibrium species in phase G.…”
Section: Case Studymentioning
confidence: 99%
“…19 Three cases are considered, namely, (i) measurements of all species in both phases, (ii) measurements of the kinetic species and equilibrium components in the phase where the instantaneous equilibria take place (phase G), and (iii) measurements of a mix of kinetic species, equilibrium components, and equilibrium species in phase G.…”
Section: Case Studymentioning
confidence: 99%
“…The detailed kinetics for the synthesis of di‐ n ‐butyl sulphide using phase transfer catalyst was explained assuming a pseudo‐first‐order reaction in 1‐bromobutane by Wang and Tseng . Oxidation of BA using sodium hypochlorite using phase transfer catalyst has been studied by several researchers, both theoretically and experimentally . Some of these studies involve experiments with a flat interface …”
Section: Introductionmentioning
confidence: 99%
“…[12] Oxidation of BA using sodium hypochlorite using phase transfer catalyst has been studied by several researchers, both theoretically and experimentally. [8,[13][14][15][16] Some of these studies involve experiments with a flat interface. [8] In this work we follow Bhattacharya and Mungikar [2] and Chen et al [11] and assume the reactions in the aqueous phase to be fast and the species to be in equilibrium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction rate of PTC assisted alkaline hydrolysis of n ‐butyl acetate and oxidation of benzyl alcohol in an agitated vessel was analyzed by Asai et al . The investigation revealed that overall reaction rate was proportional to the interfacial concentration of the actual reaction components.…”
Section: Introductionmentioning
confidence: 99%